2010
DOI: 10.1111/j.1365-2966.2010.17457.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of primary and secondary particles in galaxy clusters by compressible MHD turbulence: from radio haloes to gamma-rays

Abstract: Radio observations discovered large‐scale non‐thermal sources in the central Mpc regions of dynamically disturbed galaxy clusters (radio haloes). The morphological and spectral properties of these sources suggest that the emitting electrons are accelerated by spatially distributed and gentle mechanisms, providing some indirect evidence for turbulent acceleration in the intergalactic medium (IGM). Only deep upper limits to the energy associated with relativistic protons in the IGM have been recently obtained th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 153 publications
(355 reference statements)
13
177
0
Order By: Relevance
“…Specifically, the emission of the relic could be projected on the halo emission causing a flattening of the spectrum at higher frequencies. We also note that recent modeling of turbulent re-acceleration of relativistic protons and their secondaries in the ICM predict a flattening of the synchrotron spectrum of radio halos at higher frequencies (Brunetti & Lazarian 2011). In these models the flattening marks the transition between the spectral component due to turbulent re-acceleration and the underlying spectrum generated by the continuous injection of secondary electrons; the spectral shape of A2256 would constrain the turbulent acceleration time-scale 0.5 Gyr.…”
Section: Radio Halomentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the emission of the relic could be projected on the halo emission causing a flattening of the spectrum at higher frequencies. We also note that recent modeling of turbulent re-acceleration of relativistic protons and their secondaries in the ICM predict a flattening of the synchrotron spectrum of radio halos at higher frequencies (Brunetti & Lazarian 2011). In these models the flattening marks the transition between the spectral component due to turbulent re-acceleration and the underlying spectrum generated by the continuous injection of secondary electrons; the spectral shape of A2256 would constrain the turbulent acceleration time-scale 0.5 Gyr.…”
Section: Radio Halomentioning
confidence: 99%
“…Relativistic electrons in the ICM can be re-accelerated in situ through interaction with turbulence generated in the ICM by cluster-cluster mergers (Brunetti et al 2001;Petrosian 2001), or secondary electrons can be continuously injected in the ICM by inelastic collisions between relativistic and thermal protons (Dennison 1980;Blasi & Colafrancesco 1999;Dolag & Enßlin 2000;Enßlin et al 2011). Models considering a combination of the two mechanisms, namely the re-acceleration of both relativistic protons and their secondaries by magnetohydrodynamical turbulence generated in the ICM have been recently considered (Brunetti & Blasi 2005;Dolag et al 2008;Brunetti & Lazarian 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming these constraints, it has been suggested that during cluster mergers the re-acceleration of secondary electrons by compressible MHD turbulence can generate synchrotron radiation in good agreement with radio halos, while synchrotron emission ∼10 times fainter is generated in dynamically relaxed clusters when turbulence is dissipated (Brunetti & Lazarian 2011b). This theoretical conjecture is consistent with the observed radio bimodality in galaxy clusters (e.g., Brunetti et al 2009;Cassano et al 2010a), although it predicts a level of emission (from pure secondaries) in relaxed clusters that is close the upper limits derived for these clusters from present radio observations.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these components is still unclear and a subject of lively debate. Potentially these components contribute to the energy of the ICM and drive complex physical processes that may significantly alter our present (simplified) view of the ICM (Schekochihin et al 2005;Subramanian, Shukurov, & Haugen 2006;Brunetti & Lazarian 2011).…”
Section: Galaxy Clusters and Large-scale Structurementioning
confidence: 99%
“…Instead, there must be a pre-existing population of relativistic (or suprathermal) seed particles that are then reaccelerated by turbulent acceleration during mergers. One possibility is that the seeds are secondary electrons generated by collisions between CRs and thermal protons (Brunetti & Blasi 2005;Brunetti & Lazarian 2011). These hybrid models predict that Mpc-scale synchrotron emission from secondary electrons ('pure hadronic haloes') must also be present in relaxed clusters, with a radio luminosity 10-20 times smaller than that of merging clusters (Brunetti & Lazarian 2011).…”
Section: Radio Haloesmentioning
confidence: 99%